Finanças comportamentais : um estudo sobre o perfil do investidor, o efeito aversão a extremos e o excesso de confiança nas decisões de investimento - Vieira, Thais Roberta Correa (2012)
The classical economic theory assumes that people make decisions through rational processes, particularly in the sense that they are coherent and consistent. However, many experimental studies indicate violations of this assumption. Two factors that lead